Pengembangan Minuman Probiotik dengan Fermentasi Spontan Berbahan Apel Manalagi dari Beberapa Daerah di Provinsi Jawa Timur, Indonesia - Anggita, Diah Yasmin; Sukardi, Sukardi; Elianarni, Dahlia (Food Technology and Halal Science Journal, 2025)
Probiotic beverages are products enriched with lactic acid bacteria (LAB), which are beneficial for digestive health. Manalagi apples were chosen as the raw material due to their rich nutritional content and potential as an affordable alternative for probiotic drink production. Manalagi apples are widely found in various regions of Indonesia, particularly in Batu City, Malang Regency (Poncokusumo District), and Pasuruan Regency (Nongkojajar District). This study aimed to analyze the effects of Manalagi apples from Batu, Malang, and Pasuruan on the characteristics of apple probiotic beverages. The research was designed using a factorial Randomized Block Design (RBD) consisting of two factors with three repetitions for each treatment. The first factor was the cultivation area of Manalagi apples, including plantations in Batu (A1), Poncokusumo (A2), and Nongkojajar (A3). The second factor was the fermentation duration: 3 days (T1), 6 days (T2), 9 days (T3), 12 days (T4), and 15 days (T5). The results showed that fermentation time significantly influenced pH, total titratable acidity, lactic acid bacteria count, total sugar, total dissolved solids, and antioxidant activity. The best treatment for this apple probiotic drink was found in sample A3T5, which used Nongkojajar apples with a 15-day fermentation period.